Pengaruh Model Pembelajaran Tai Berbantuan Flip Chart Terhadap Sikap Peduli Sosial dan Tanggung Jawab Siswa SD Kelas III SDN Harjosari 01 Bawen - Nur Rokhmah; Kartika Yuni Purwanti (Journal on Education, 2024)
The purpose of this study was to determine the effect of the flip chart-assisted TAI type learning model on social care attitudes and responsibilities of third grade elementary school students at SDN Harjosari 01 Bawen. This study uses a quantitative approach with the type of experimental method, namely Quasi Experimental Design with the form of a Non-Equivalent Control Group Design. The population in this study were all third grade students at SDN Harjosari 01 Bawen. As for the sample in this study were students in class III A and students in class III B SDN Harjosari 01 Bawen. Data collection techniques using observation, questionnaires, unstructured interviews and documentation. The data analysis technique used is Normality Test, Homogeneity Test, Independent Sample T-Test and Simple Linear Regression Test. The results of this study indicate that: 1) There are differences in the use of flip chart-assisted TAI-type learning models for students' social care attitudes, which can be seen from the results of the Independent Sample T-Test and the obtained t count > t table (3.353 > 2.016) with the sig-(2-tailed) value is 0.002 <0.05, then Ho is rejected and Ha is accepted. 2) There is a difference in the use of the flip chart-assisted TAI type learning model for the attitude of student responsibility, which can be seen from the results of the Independent Sample T-Test and the obtained t count > t table (2.427 > 2.016) with a sig-(2- tailed) ie 0.019 <0.05, then Ho is rejected and Ha is accepted. 3) There is an effect of using the flip chart-assisted TAI type learning model on students' social care attitudes, which can be seen from the results of the Simple Linear Regression Test and a significance level of 0.002 <0.05 is obtained with a percentage R Square value of 0.207 = 20.7% , then this regression model can affect the participation variable. 4) There is an effect of using the TAI type learning model assisted by flip charts on the attitude of student responsibility, which can be seen from the results of the Simple Linear Regression Test and a significance level of 0.002 <0.05 is obtained with a percentage R Square value of 0.120 = 12%, then This regression model can affect the participation variable. So it can be concluded that the flip chart-assisted TAI type learning model has an effect on social care attitudes and responsibilities of Class III Elementary School students at SDN Harjosari 01 Bawen.